Флористичний склад, поширення та ботаніко-географічна характеристика деревно-чагарникових видів у садах і парках колишніх залізних рудників Криворіжжя - Savosko, V.M.; Tovstoljak, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to analyze the floral composition, distribution and botanico-geographical characteristics of woody and shrubby species in the gardens and parks of the former iron mines at Kryvorizhzhya depending on their current status. Material and methods. During 2015–2016 seven existing parks (“Ternivskyi”, “Shakhtarskyi”, “Zatyshnyi”, Suvorov sports park, park near the Palace of Culture of mine “Rodina”, “Saksahanskyi”, “Rudanivskyi”), the abandonment park in the exclusion zone (Park of mine “Hvardiiska”), the garden of hotel “Park House” by traditional methods were explored. The nomenclature of taxa is given by S.K. Cherepanov (1995), according to the International Index of Scientific Names of Plants (2017), a geographical analysis – by A.L. Taktajan (1978). Results. The gardens and parks of the former iron mines of Kryvorizhzhya in 1930–1970 years were the basis of the green plantations of the region, and since the 1980s they have been gradually changing their social status. At the beginning of the XXI century: the garden of the Park House hotel is in private ownership, “Shakhtarskyi” and “Saksahanskyi” parks are the city’s parks, Park Ternovskiy is the main park of the microdistrict. They are actively visited, their territory is well-groomed. Parks “Zatyshnyi”, near the Palace of Culture of mine “Rodina” and “Rudanivskyi” are less popular for visitors, secondary to the balance holders and partially groomed. Suvorov sports park and especially the Park of mine “Hvardiiska” are in fact destructured and degraded. The floristic composition oh the tree of shrubs includes 93 species and cultivars, which belong to 53 genera and 27 families. The share of gymnosperms is about 18 %. Leading families are Rosaceae (16 species), Saliceae (9), Oleaceae (7), Aceraceae (7) and Pinaceae (6). Leaders of the genus among Pinophyta – Juniperus (4 species and cultivar), Thuja (4), Picea (3), among Magnoliophyta – Acer (7), Populus (7), Ulmus (4). Conclusions. The greatest species diversity is found in the “Shakhtarskyi” and “Ternivskyi” parks, which are characterized by considerable social status and demand, as well as maximum areas. Less species diversity is found in plantations, the most abandoned and gradually degrading – Suvorov sports park and Park of mine “Hvardiiska”. Introduced wood and shrub species significantly prevail over native species. These species mainly originate from the Circumboreal, Atlantic-North American and Mediterranean floristic regions.